Faktor – Faktor yang Berhubungan dengan Status Gizi pada Anak Usia 0-23 Bulan Berdasarkan Composite Index of Anthropometric Failure (CIAF) di Wilayah Kerja Puskesmas Karangayu Kota Semarang - Erlita Nur Andini; Ari Udiyono; Dwi Sutiningsih; Moh Arie Wuryanto (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2020)
Background: According to UNICEF, half of all deaths of children are caused by malnutrition. The conventional anthropometric index to measure nutritional status is unable to measure the overall prevalence of malnutrition and multiple malnutrition. The solution is to measure it using the Composite Index of Anthropomeric Failure (CIAF). The aim of the study was to analyze the factors that affect the nutritional status of children aged 0-23 months based on Composite Index of Anthropomeric Failure (CIAF).Methods: This research was an observational analytic study with cross-sectional study design. This research was conducted in the working area of Karangayu Health Center with 231 study sample of mothers who have 0-23 months old children (population used as sample). Chi-square and fisher exact test were used as statistical test.Result: Factors associated with the nutritional status of children aged 0-23 months based on the Composite Index of Anthropometric Failure (CIAF) were the age of the child (p=0,029); birth length (p=0.005); maternal age during pregnancy (p=0.002); maternal height (p=0.025); gestational age of maternal (p=0.049). While factors unassociated were gender (p=0.997), birth weight (p=0.316), nutritional status of the mother during pregnancy (p=0.232), maternal employment (p=0.614), and education level (p=0.951).Conclusion: Age of child, birth length, maternal age during pregnancy, mother’s height, and gestational age of maternity mothers were factors associated with nutritional status of 0-23 months old children based on CIAF. A dominant factor that affected the nutritional status of children aged 0-23 months was the mother's age during pregnancy.